Bicuspidisation: Two is Better than None - A Case Report - Ranjit, Rebicca; Manandhar, Pratik; Bista, Soni (Journal of Nepalese Society of Periodontology and Oral Implantology, 2021)
A periodontally compromised tooth with severe furcation involvement may as well be retained of their roots rather than its removal in toto. Bicuspidisation (Premolarisation) is a surgical technique of sectioning mandibular molar roots with their respective crown portions followed by rehabilitation with fixed prosthesis in the individual segments. This not only eliminates furcation involvement but also facilitates effective oral hygiene maintenance. The present case report demonstrates the successful management of grade III furcation involved mandibular molar by bicuspidisation followed by subsequent prosthodontic rehabilitation. It gives a better alternative to salvage a periodontally compromised tooth rather than opting for extraction.